CURRICULUM, CHILD AND CHILDHOOD: BETWEEN DIFFERENT VOICES - Gicele Maria Cervi; Monique Cristina Francener Hammes Schütz (Universidade Estadual Paulista Júlio de Mesquita Filho, 2016)
The purpose of this paper was to analyze, from legal documents and discursive practices of the teachers, concepts of child, childhood, and curriculum. The research approach is qualitative. It's about a field research was performed data collection along with the legal documents and two teachers of early childhood education and two teachers of first grades of elementary school from the municipal education network of Blumenau, Santa Catarina, in 2014. The results of the research demonstrate the syntony of the speech of teachers with legal documents, the distance between the early childhood education and the elementary school. They also presented the strength of the statements of psychology and medicine in the discursive practices of the interviewed teachers and legal documents, the fragility on the conceptions of child and curriculum, of interviewed teachers and the intensification of the level of education, along with the extension of the craft of student of the young children. We realized that the discussion on curriculum does not cross the every day of interviewed teachers and, the child when making the transition from the early childhood education to the elementary school becomes a student. Keywords: Child. Curriculum. Early Childhood Education. Elementary School. Childhood.